2004
DOI: 10.1176/appi.psy.45.5.386
|View full text |Cite
|
Sign up to set email alerts
|

Interrater Reliability, Prevalence, and Relation to ICD-10 Diagnoses of the Diagnostic Criteria for Psychosomatic Research in Consultation-Liaison Psychiatry Patients

Abstract: The Diagnostic Criteria for Psychosomatic Research (DCPR) have been proposed by an international group of psychosomatic investigators as an operationalized tool for the assessment of psychological distress in medical patients. The aims of the present study were to evaluate interrater reliability, the distribution of DCPR syndromes, and their relationship with ICD-10 diagnostic categories. One hundred consecutive patients who were referred for psychiatric consultation in a university general hospital consented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 30 publications
6
66
0
2
Order By: Relevance
“…The findings suggest that demoralization is quite prevalent among the medically ill and that it is distinct and not hierarchically related to major depressive disorder 45 . The dis-tinction between demoralization and major depressive disorder was confirmed in other clinical populations 46 , including patients with skin diseases 47 and consultation-liaison psychiatry patients 48 . In a sample of heart transplanted patients, demoralization was significantly associated with a decrease in specific dimensions of psychological well-being and the co-occurrence of major depressive disorder did not alter those associations 49 .…”
Section: Major Depressive Disordermentioning
confidence: 74%
“…The findings suggest that demoralization is quite prevalent among the medically ill and that it is distinct and not hierarchically related to major depressive disorder 45 . The dis-tinction between demoralization and major depressive disorder was confirmed in other clinical populations 46 , including patients with skin diseases 47 and consultation-liaison psychiatry patients 48 . In a sample of heart transplanted patients, demoralization was significantly associated with a decrease in specific dimensions of psychological well-being and the co-occurrence of major depressive disorder did not alter those associations 49 .…”
Section: Major Depressive Disordermentioning
confidence: 74%
“…Furthermore, preliminary data examining the DT and the HADS compared with the International Classification of Diseases, Tenth Revision (ICD-10) in Italian cancer patients seem to confirm validity of both psychological tools [36]. It also has to be considered that even gold standard psychiatric nosographic systems [e.g., Diagnostic and Statistical Manual for Mental Disorders-Fourth Revision (DSM-IV) and ICD-10] lack criteria for the identification of some important dimensions of psychosocial morbidity (e.g., health anxiety, demoralization, irritable mood) in medically ill patients, including cancer patients [37,38]. Bearing these limitations in mind, the findings of the study showed that both the DT and the MT were useful in rapidly assessing psychosocial distress in cancer patients in a different cultural area in comparison with English-speaking countries.…”
Section: Discussionmentioning
confidence: 94%
“…This is not a new finding. In fact, previous studies suggested that demoralization can be found in major depression: Klein 37 claimed that demoralization may develop in ''endogenomorphic depression'', and Galeazzi et al 30 and Mangelli et al 10 observed demoralization in more than 50% of medically ill patients with major depression. In a study conducted by Marchesi and Maggini 38 , the presence of major depression was related to an increase of demoralization scores.…”
Section: Discussionmentioning
confidence: 99%
“…The interview for DCPR consists of 58 items scored in a yes/no response format evaluating the presence of 1 or more of 12 psychosomatic syndromes. The interview has shown excellent inter-rater reliability, construct validity, and predictive validity for psychosocial functioning and treatment outcome 30 .…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation